2020
DOI: 10.21873/cgp.20215
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Drug Sensitivity Polymorphisms in Stage III Non-small Cell Lung Cancer With Invasion of Mediastinal Lymph Nodes

Abstract: Background/Aim: Patients with stage IIIA (N2) non-small cell lung cancer (NSCLC) with no progression after induction chemotherapy are usually selected for surgery. Nowadays, response to chemotherapy is not predictable. We aimed to identify genomic predictive markers for response to induction chemotherapy in stage IIIA (N2) NSCLC patients. Patients and Methods: Whole-exome sequencing (WES) was performed on samples from 11 patients with no response after induction chemotherapy and 6 patients with documented path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The unique risk value for each LC patient was calculated based on the risk score formula. Among of them, NCBP2 has the maximum weighting coefficient and has been reported to interfere with the drug sensitivity of platinum in non-small cell lung cancer [ 31 ]. Then, LC patients were divided into low-risk group and high-risk group according to the median value of the risk score (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The unique risk value for each LC patient was calculated based on the risk score formula. Among of them, NCBP2 has the maximum weighting coefficient and has been reported to interfere with the drug sensitivity of platinum in non-small cell lung cancer [ 31 ]. Then, LC patients were divided into low-risk group and high-risk group according to the median value of the risk score (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A variant in GBA has been shown to cause alternative splicing leading to Gaucher disease [40], so the possibility of GBA2 mutations leading to over production of inactive isoforms should be considered. Although nonpathological variants of GBA2 have rarely been described [41], recently it was reported that GBA2 variants are predictive for response to chemotherapy in non-small-cell lung cancer [42]. Further studies should be considered to see whether these variants affect activity or alternative splicing.…”
Section: Discussionmentioning
confidence: 99%
“…Patient groups. The patient inclusion and exclusion criteria have already been published in extenso (15,16).…”
Section: Methodsmentioning
confidence: 99%
“…There were no differentially expressed genes between responders versus non-responders, but the main pathways differentially expressed between groups were cytokine pathways, focal adhesion or extracellular matrix receptor interaction. We also performed whole-exome sequencing (WES) of preoperative tumoral samples from 16 patients (16) and identified SNPs that associated with response to chemotherapy in NSCLC stage IIIA (N2). A higher alternative allele frequency was found on SENP5, rs63736860, rs1602 and NCBP2, rs553783 in the non-responder group, and on RGP1, rs1570248, SLFN12L, rs2304968, rs9905892, and GBA2, rs3833700 in the responder group.…”
mentioning
confidence: 99%